Problem Based Learning Model on Mathematical Communication Skills and Learning Interest Based on Initial Abilities of Fifth Grade Elementary School Students - Haidir; Ahmad Fauzan; Syafri Ahmad; Alwen Bentri (Universitas Pendidikan Ganesha, 2025)
The low interest in learning and mathematical communication skills among elementary school students remains a problem that impacts their understanding of mathematical concepts. Students often struggle to express mathematical ideas orally or in writing. This study aims to analyze the effectiveness of the problem-based learning (PBL) model in enhancing students' mathematical communication skills and learning interests, considering their initial abilities. The method employed was a quasi-experimental design with a 2 × 2 factorial structure, and data analysis was conducted using two-way ANOVA. This study employed two samples: the experimental class and the control class. Sampling in this study used the Probability Sampling technique. The experimental class consisted of 20 students, and the control class consisted of 25. The results showed that the PBL model significantly improved students' mathematical communication skills and learning interests, especially in students with low initial abilities. There was an interaction between the learning model and initial abilities on both variables. These findings concluded that the PBL model is effective in addressing the problem of low mathematical communication and student learning interests. The implications of this study suggest that PBM can be utilized as an alternative learning strategy to support the achievement of mathematical competencies in elementary schools.